2009
DOI: 10.1159/000197116
|View full text |Cite
|
Sign up to set email alerts
|

Recent Therapeutic Strategies Improve Renal Outcome in Patients with IgA Nephropathy

Abstract: Background/Aims: Various treatment options for IgA nephropathy (IgAN) have been developed, particularly over the past decade. Nevertheless, whether such therapeutic interventions improve actual renal outcome as compared with previous therapies remains obscure. Methods: We examined data from 304 patients with IgAN whose serum creatinine value at renal biopsy was <2.0 mg/dl and who had been followed up for >12 months. We assigned the patients to groups according to the period of diagnosis (group E, between 1981 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
28
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 46 publications
3
28
1
Order By: Relevance
“…24 In this study, the treated group showed a lower estimated GFR at baseline compared to control group. However, the treated group that was expected to have the worst prognosis, [25][26][27] had a significant reduction of proteinuria levels.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…24 In this study, the treated group showed a lower estimated GFR at baseline compared to control group. However, the treated group that was expected to have the worst prognosis, [25][26][27] had a significant reduction of proteinuria levels.…”
Section: Discussionmentioning
confidence: 93%
“…However, prospective, randomized controlled trials to evaluate treatment of primary IgA nephropathy are few, and most studies have used approaches similar to the present study. 27 Finally, the present study focused on the effects during the first 12 months of treatment, and this time is not long enough to study the efficiency of this treatment to preserve renal function. For this effect would be necessary 5 to 10 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Samples from patients with aCI were obtained from Chiba Prefectural Sawara Hospital. Samples from patients with CKD were from the Kumamoto cohort [15,16].…”
Section: Patient and Healthy Donor (Hd) Seramentioning
confidence: 99%